Stunting in the Context of Plenty: Unprecedented Magnitudes Among Children of Peasant's Households in Bukombe, Tanzania - Shilugu, Lucas L.; Sunguya, Bruno F. (Frontiers in Nutrition, 2019)
Background: Children of peasant households are perceived to be protected from undernutrition owing to perceived food security. However, evidence points to increased vulnerability that is not even in low- and middle-income countries—Tanzania is no exception. We examined magnitude and factors associated with stunting among underfive children from peasant’s households and compare them with those of other households in a rural district in Tanzania. Methods: This cross-sectional study was conducted in Bukombe district in Tanzania among the randomly selected 358 pairs of underfive children and their caregivers. Data was collected through face-to-face interviews and measuring anthropometric measurements. Data was analyzed using both descriptive and logistic regression methods while comparing stunting status between children from peasants’ households compared to those whose households’ major other economic activities. Results: Stunting was prevalent in 52.8% of underfive children in Bukombe district–a higher burden compared to the national average. Evidence further showed higher vulnerability of children from peasant households to other households (56% vs 46%). This was likely contributed by poorer feeding practices amongst the peasant households. For example, about 71% of households of peasants fed their children with lower dietary diversity compared to 55% of other households (p=0.003). Other factors associated with stunting in this district included older underfive (AOR =2.74, p =0.003), household with severe food insecurity (AOR =3.34, p =0.002), and children with low birth weight (AOR =0.31, p =0.02). Conclusion: Despite their households’ engagement in farming that could ensure household’s food security, children of peasants succumb to higher magnitude of stunting compared to others in Bukombe district. In addressing this and other chronic forms of undernutrition in Tanzania and areas with similar context, efforts should also be streamlined to this population and focus on interventions to address poor feeding practices, food insecurity, and extending such efforts to the first 1000 days to ameliorate low birth weight.